Current Treatment Options for Nonalcoholic Fatty Liver Disease and Nonalcoholic Steatohepatitis - Melanie D Beaton (Canadian Journal of Gastroenterology)
Nonalcoholic fatty liver disease is the leading cause of liver disease in western society. It is a cause of end-stage liver disease, with increased mortality secondary to cirrhosis and its complications. It is also recognized that cardiovascular disease is a significant cause of death in these patients. Significant work evaluating various treatments has been performed in recent years; however, to date, no ideal therapy exists. Lifestyle modification remains the cornerstone of management. The present article reviews the current status of various treatment modalities evaluated in nonalcoholic fatty liver disease.